2021
DOI: 10.11591/ijere.v10i1.20813
|View full text |Cite
|
Sign up to set email alerts
|

CORE learning model: Its effectiveness towards students’ creative thinking

Abstract: The research has been carried out at the Islamic junior high school of East Lampung to determine the effectiveness of the Connecting, Organizing, Reflecting, and Extending (CORE) learning model on students’ creative thinking skills on sound waves topic. The research method used was a quasi-experimental design with Non-Equivalent Control Group Design. Data on creative thinking skill were collected using essay test instrument. This research was conducted on the eighth-grade students of an Islamic senior high sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 10 publications
0
18
0
3
Order By: Relevance
“…Five important ability indicators were also developed at the level of self-development ability, namely, career development, practical reflection, self-reflection, joint learning, and communication skills. These are similar to those expected of ideological and political educators by society, namely, to master the basic methods of disciplinary research and educational science research, have the ability to find and analyse problems, and understand the role of a community of common learning (Christof, 2014;Fabriz et al, 2021;Karatas & Yilmaz, 2021;Saregar, 2021).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Five important ability indicators were also developed at the level of self-development ability, namely, career development, practical reflection, self-reflection, joint learning, and communication skills. These are similar to those expected of ideological and political educators by society, namely, to master the basic methods of disciplinary research and educational science research, have the ability to find and analyse problems, and understand the role of a community of common learning (Christof, 2014;Fabriz et al, 2021;Karatas & Yilmaz, 2021;Saregar, 2021).…”
Section: Discussionmentioning
confidence: 67%
“…This is consistent with the hope of the state and society that students have a certain sense of reflection, critical thinking, team spirit, etc. (Christof, 2014;Saregar, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Keterampilan berpikir seperti berpikir kritis dan kreatif sangat berharga yang akan semakin dibutuhkan karena meningkatnya masalah kompleks yang disebabkan oleh perkembangan teknologi dan gerakan sosial yang pesat di seluruh dunia (Saregar et al, 2021;Suyidno et al, 2019;Yani et al, 2021). Oleh karena itu, pendidik harus mengajarkan keterampilan berpikir ini kepada peserta didiknya agar dapat sukses sebagai warga negara masa depan.…”
Section: Pendahuluanunclassified
“…At the validation stage of this model, it showed that the problems encountered at the beginning of the model preparation were proven, namely the lack of teacher ability in providing rhythmic activity learning in the PE learning process in elementary schools [29]. The courage of teachers to apply various rhythmic activity learning models is still low so students have difficulty in carrying out rhythmic activity movements because of the lack of movement obtained.…”
Section: Phase 3 Model Validationmentioning
confidence: 99%